2017
DOI: 10.1142/s2251237317500010
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Water Oxidation Using {PMo12O40@Mo72Fe30}n Based Soft Oxometalate

Abstract: Finding an alternative energy resource which can produce clean energy at a low cost is one of the major concerns of our times. The conversion of light energy into chemical energy is one key step forward in the direction. With that end in view photochemical water oxidation to produce oxygen plays a crucial role. In the present paper we have synthesized a soft oxometalate fPMo 12 O 40 @Mo 72 Fe 30 g n (1) from its well-known precursor polyoxometalate constituent [Muller et al., Chem. Commun. 1, 657 (2001)]. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Most PSTMCs are studied under electrochemical conditions for either nitrate/bromate reduction or ascorbic acid oxidation . POM-based soft-oxometalates have been explored for various electrochemical catalytic processes such as electrochemical CO 2 reduction or water oxidation . Our group has initiated PSTMCs for their electrocatalytic activity in the OER/HER .…”
Section: Introductionmentioning
confidence: 99%
“…Most PSTMCs are studied under electrochemical conditions for either nitrate/bromate reduction or ascorbic acid oxidation . POM-based soft-oxometalates have been explored for various electrochemical catalytic processes such as electrochemical CO 2 reduction or water oxidation . Our group has initiated PSTMCs for their electrocatalytic activity in the OER/HER .…”
Section: Introductionmentioning
confidence: 99%
“…They can be formed by replacing 30 Mo 2 O 4 Ac linkers in {Mo 132 } with 30 Fe aq 3+ in crystalline forms including discrete molecules, interconnected one-dimensional chains, or two-dimensional layers. , They can also be prepared directly by mixing acidic solutions of FeCl 3 and NaMoO 4 , producing immediately an amorphous phase of cluster . {Mo 72 Fe 30 } can be used as a unique shell for hosting some clusters such as Lindqvist and Keggin polyoxomolybdates in both reduced and oxidized forms. They have been limitedly used as catalysts for the growth of monolayer carbon nanotubes, water oxidation, and oxidation of sulfides, alcohols, and olefins. Just recently, we functionalized its surface with amino groups in a controlled manner …”
Section: Introductionmentioning
confidence: 99%
“…POMs are generally ionic in nature with high charge and a number of hydrogen bonding sites, which provides the possibility to synthesize composites with different electro active surfaces such as graphene, graphene oxide, different LDHs ,. The immobilization of the POM moiety on the electro active surface can enhance the catalytic activity of these materials ,. POMs can also exist in a colloidal state of soft‐oxometalates (SOMs) .…”
Section: Introductionmentioning
confidence: 99%
“…POMs can also exist in a colloidal state of soft‐oxometalates (SOMs) . We have recently shown that soft oxometalates based on several different oxometalates can act as active catalyst for photo chemical oxidation of water without the need of a photosensitizer and a sacrificial electron donor , Further CO 2 can be transformed into other energy dense organic compounds like formic acid and formaldehyde by H 2 O in presence of light using SOMs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation